KONTROVERSI EKSISTENSI FASHL DI ANTARA KOMPONEN IDHAFAH - Muhammad Al Farabi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
The conclusion of this research is that the existence of fashl (separator) between mudhaf and mudhaf ilaîh contained in the qiraah of Ibn 'Âmir is a way that is accommodated by one of the Arabic syntactic opinions. Specifically, because mudhâf and mudhâf ilaîh are manzilah syaî´ wâhid (one unit), the presence of fashl between the two is not allowed. However, the qiraah of Ibn ʻmir asy-Syâmî narrated fashl between mudhaf and mudhaf ilaîh where the transmission is valid and has the argument that fashl between mudhaf and mudhaf ilaîh can in fact be found in the kalam of the Arabs